ANALISIS BEBAN KERJA PADA PEKERJAAN BAJA BERAT DAN PENUTUP ATAP SEBAGAI DASAR DALAM PEMERATAAN TENAGA KERJA DENGAN METODE WORKLOAD ANALYSIS (WLA) - Maria Olivia Septiana; Waluyo Nuswantoro; Subrata Aditama Kittie Aidon Uda (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2026)
The success of a project is determined by strict time constraints accompanied by the need to maintain the required building quality standards within a dynamic environment. However, the pressure to meet these schedule requirements increases workers' workloads, which ultimately leads to work fatigue. The implementation period of the Maranatha Church Construction Project was 120 days, which is relatively short compared to similar building projects that generally require 180 to 360 days, depending on the building area, design complexity, construction methods, and availability of resources. Therefore, this project demonstrates a relatively high level of schedule efficiency. This accelerated schedule created considerable work pressure, particularly in heavy steel and roofing activities. Accordingly, this study was conducted to identify workers' workload levels using the Workload Analysis (WLA) method and to determine the optimal labor allocation to achieve a balanced distribution of workloads. The work sampling technique was employed for data collection to obtain objective information regarding the number of workers and their activities in carrying out the assigned tasks. The results indicate the existence of workload imbalance. Fitters (120.21%) and welders (120.75%) were classified as overloaded; therefore, the addition of one worker for each occupation is recommended to reduce their workloads to a near-optimal level. In contrast, roof workers experienced an underload condition (79.20%), and a reduction of one worker is recommended to improve cost efficiency and increase the group's productivity to 95.04%. Meanwhile, erection workers and steel workers were found to have optimal and stable workload levels.